Structure, photo- and electroluminescence of silicon dioxide implanted with high fluensies of tin ions - Romanov, Ivan A.; Makhavikou, Maxim A.; Komarov, Fadei F.; Milchanin, Oleg V.; Parkhomenko, Irina N.; Vlasukova, Liudmila A.; Wendler, Elke; Mudryi, Alexander V.; Zhivulko, Vadim D. (Journal of the Belarusian State University. Physics, 2019)
Samples of SiO2/Si have been implanted with tin ions (200 and 80 keV, 5 ⋅ 1016 and 1 ⋅ 1017 cm-2) at room tempera- ture and afterwards annealed at 800 and 900 °C for 60 min in air ambient. The structural and light emission properties of (SiO2 + Sn-based nanoclusters) composites have been studied using Rutherford backscattering spectroscopy, transmission electron microscopy in cross-section geometry, photo- and electroluminescence. For the as-implanted samples it has been shown the formation of metal β-Sn nanoclusters layer in oxide matrix. The heat treatment in oxidation ambient results in structural transformation of implanted layers. The initially flat surface of the sample becomes irregular (wave-like) and dendrites are formed in subsurface region of oxide film. The appearance of dendrites is most probably due to the SnO2 phase formation. Strong «violet» photo- and electroluminescence (∼3.1 eV) is observed for SiO2/Si sample after annealing. One could conclude from photo- and electroluminescence spectra correlation that the emission centers are the same for the both cases. The nature of the observed emission is discussed.
Keywords: SiO2 films; high-fluence Sn implantation; annealing in air; nanoclusters; photo- and electroluminescence